The Role of Istighosah and Tahlil Congregation-Based Sharia Cooperatives (Case Study of Istighosah Congregation in Tanjungsari Village, Wanasari District, Brebes Regency) - Ahmad Faqih Udin (ProBisnis : Jurnal Manajemen, 2023)
The role of sharia cooperatives includes building and developing the potential and abilities of members of the istighosah and tahlil congregations and society in general to improve their socio-economic welfare. In addition, sharia cooperatives can act as a center for Muamalah activities aimed at implementing and developing the national economy based on the principle of kinship and economic democracy. The rise of usury in Muamalah, especially in terms of credit and investment, as well as big businesses that dominate the economy make it difficult for small traders to develop and compete. This causes a decline in the economic level of society. Sharia cooperatives have great potential, both in terms of human resources and other supports, but there are still many sharia cooperatives that do not function optimally. The results of this study indicate that the istighosah-based Islamic Cooperative Society was established with the aim of strengthening ukhuwah Islamiyah, the spirit of mutual cooperation, and increasing the welfare and prosperity of the community. So far, this sharia cooperative has done a lot to meet the needs of its members and improve the economy, most of whom are congregations of Istighosah and Tahlil Tanjungsari Village.